Considering distribution grids and local flexibilities in the prospective development of the European power system by 2050. (15th July 2020) - Allard, Stéphane; Debusschere, Vincent; Mima, Silvana; Quoc, Tuan Tran; Hadjsaid, Nouredine; Criqui, Patrick
Highlights: A global assessment approach for the European power system development up to 2050. European long-term energy system outlook combine with grid investment and dispatch. Grids evolution under a 2 °C climate change policy relevant for policy makers. Assessing impacts on the CO2 emissions and the development of the grid infrastructure. Local flexibility solutions influence the evolution of the European power system. Abstract: Previous works proposed a tool coupling models of a prospective outlook on long-term energy systems and a transmission grid investment and dispatch, focusing on the representation of the European transmission grid and its development on the horizon 2050–2100. In this paper, this prospective tool is further improved with the capacity to compute voltage as well as active and reactive power flows at the level of the distribution grid. This added capacity allows analyzing various issues related to the integration of variable energy resources in three representative real medium voltage distribution grids (urban, rural and semi-urban). Technical flexibility solutions such as on-load tap changers, variable energy resources curtailment and storage technologies are modeled and compared to reinforcement. A cost comparison between these flexibility solutions is also carried out. Finally, the new version of the tool is used to evaluate the CO2−eq emissions linked to the development of the European power system infrastructure, with flexibility solutions, up to the year 2050 (both high voltage alternative and direct current lines reinforcement being considered) under a 2 °C climate energy policy scenario. Results show that it exists various options for the development of the European grid infrastructure, which are clearly sensitive to the level of accuracy in the representation of the physical infrastructures and their technical limitations. Being able to represent the distribution grid, in addition to the transmission one, has a noticeable impact on the prospective outlook of the European power systems both in terms of infrastructure reinforcement and estimation of the needs of flexibility solutions.